Dependence of Photoelectrochemical Properties on Geometry Factors of Interconnected "Caterpillar-like" ZnO Networks. (20th December 2016) - Li, Qiang; Sun, Xing; Lozano, Karen; Mao, Yuanbing
Highlights: Hierarchical "caterpillar-like" ZnO nanostructures have been prepared through a hybrid route. The ease and high throughput of the method favors a feasible PEC applications. The tunability of the geometric factors could optimize the light-material interaction. Ultralong and ultrathin branches shorten minority carrier diffusion lengths to further improve PEC performance. Abstract: To elevate the spatial occupancy of one-dimensional ZnO nanostructures and overcome the limitations of multistep seeding methods currently widely used, a rational, facile and high-yielding procedure has been reported by our group previously for the fabrication of the interconnected three-dimensional "caterpillar-like" ZnO nanostructured networks (CZNs) for photoelectrochemical applications. In this work, by manipulating their growth process, we investigated the dependence of their photoelectrochemical properties on geometry factors of these unique CZNs consisting of branched ZnO nanowires onto ZnO nanofibers with tunable surface-to-volume ratio and roughness factor. They offer mechanically and electrically robust interconnected networks with open micrometer-scale structures and short hole diffusion length. We further studied the preferential light-material interaction and charge separation to maximize the photo-to-hydrogen conversion efficiency. When used as photoanode, our CZNs not only favor sunlight harvesting with multireflection ability, but also suppress the recombination of photogenerated charge. Compared to the literature results, our CZN photoanodes with ZnO nanobranches of ∼2.2 μm in length and ∼25 nm in diameter exhibited the highest photocurrent density of 0.72 mA ∙ cm −2 at +1.2 V (versus Ag/AgCl) and conversion efficiency of 0.209% at +0.91 V (versus RHE) without being decorated with noble metal cocatalysts or nonmetallic/metallic dopants due to their favorable structural features. Overall, our procedure to obtain the desirable CZN yields opportunities for facile and efficient fabrication of model photoelectrochemical anodes and would be applied to other materials for sustainable chemistry and engineering applications.